2015
DOI: 10.1186/s12943-015-0321-5
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis, autophagy, necroptosis, and cancer metastasis

Abstract: Metastasis is a crucial hallmark of cancer progression, which involves numerous factors including the degradation of the extracellular matrix (ECM), the epithelial-to-mesenchymal transition (EMT), tumor angiogenesis, the development of an inflammatory tumor microenvironment, and defects in programmed cell death. Programmed cell death, such as apoptosis, autophagy, and necroptosis, plays crucial roles in metastatic processes. Malignant tumor cells must overcome these various forms of cell death to metastasize. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
614
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 824 publications
(633 citation statements)
references
References 157 publications
(171 reference statements)
11
614
0
8
Order By: Relevance
“…Apoptosis is an active process that results in DNA damage, followed by cell death in the absence of inflammation (23,24). Therefore, medicines and compounds that have the capability to promote apoptosis are valuable candidates for cancer therapy (25).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is an active process that results in DNA damage, followed by cell death in the absence of inflammation (23,24). Therefore, medicines and compounds that have the capability to promote apoptosis are valuable candidates for cancer therapy (25).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy provides cell ability to adaptation and it protects the cell from apoptosis. In this way, autophagy shows the action promoting tumor metastasis [78]. From the studies on ovarian cancer xenografts, it is found that ARH1 overexpression promotes cell dormancy, which is correlated with higher level of autophagosome formation [54].…”
Section: Tumor Resistance To Anti-angiogenic Therapymentioning
confidence: 99%
“…However, defect in apoptosis can cause cancer and the suppression of apoptosis during carcinogenesis may play a crucial role in the development of some cancer types (2). Apoptosis is characterized by different morphological changes, such as cell membrane blebbing, cell shrinkage, nuclear fragmentation, chromatin condensation and chromosomal DNA fragmentation (3,4). In order to promote phagocytosis of apoptotic cells by macrophages, apoptotic cells present specific membrane morphologies to activate this process.…”
Section: Targets Of Mdr Cancer Cellsmentioning
confidence: 99%